If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 43(p + 15) = 2494 Reorder the terms: 43(15 + p) = 2494 (15 * 43 + p * 43) = 2494 (645 + 43p) = 2494 Solving 645 + 43p = 2494 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-645' to each side of the equation. 645 + -645 + 43p = 2494 + -645 Combine like terms: 645 + -645 = 0 0 + 43p = 2494 + -645 43p = 2494 + -645 Combine like terms: 2494 + -645 = 1849 43p = 1849 Divide each side by '43'. p = 43 Simplifying p = 43
| 2x+6y+75=0 | | -2p+5p=-18 | | M/-7=-14 | | 9a=10a | | 3y+y+4y= | | n^2-5n-25-125=0 | | -2m-7m=18 | | 6(-8+7x)=-90 | | 4v+28+2v=-8 | | x+5+4x-60=170 | | 8+5x=(8+5x) | | x-3-4x=21 | | -20=100-20t | | 12x+(11x-7)=-99 | | 7c-5c= | | 7x-3=3(x+1) | | 20=100-20t | | 7x-3=3(x-1) | | 2(10+3x)=62 | | 0.0000245=((0.10+x)*4x*x) | | 7b+28=6(5b-3) | | C=c+4b+3a | | 4/y=1/20 | | (1/5)n=-3 | | 3x-12=4x-48 | | 6-7n-8n+8=0 | | 4x+18=4x+5 | | -2(-1+2x)=-38 | | m=13/3 | | 3(8n+8)=120 | | 11n-6n=40 | | (3/4)m=6 |